Country data on AMR in India in the context of community-acquired respiratory tract infections: links between antibiotic susceptibility, local and international antibiotic prescribing guidelines, access to medicine and clinical outcome. (6th September 2022) - Torumkuney, Didem; Poojary, Aruna; Shenoy, Bhaskar; Nijhara, Puja; Dalal, Krunal; Manenzhe, Rendani
Abstract: Background: Antimicrobial resistance (AMR) is one of the biggest threats to global public health. Selection of resistant bacteria is driven by inappropriate use of antibiotics, amongst other factors. COVID-19 may have exacerbated AMR due to unnecessary antibiotic prescribing. Country-level knowledge is needed to understand options for action. Objectives: To review the current situation with respect to AMR in India and initiatives addressing it. Identifying areas where more information is required will provide a call to action to minimize further rises in AMR and to improve patient outcomes. Methods: National AMR initiatives, antibiotic use and prescribing in India, and availability of susceptibility data, in particular for the key community-acquired respiratory tract infection (CA-RTI) pathogens ( Streptococcus pneumoniae and Haemophilus influenzae ) were identified. National and international antibiotic prescribing guidelines for specific CA-RTIs (community-acquired pneumonia, acute otitis media and acute bacterial rhinosinusitis) commonly used locally were also reviewed, plus local antibiotic availability. Insights from a local clinician and clinical microbiologist were sought to contextualize this information. Conclusions: Many initiatives have been launched since AMR was recognized as a national priority and organizations such as the Indian Academy of Paediatrics and the Global Antibiotic Resistance Partnership have worked to build awareness. The Indian Ministry of Health and Family Welfare published a 5 year national action plan on AMR. However, the burden of infectious disease and consumption of antibiotics in India is high. There have been national surveillance studies generating local data along with international studies such as Survey of Antibiotic Resistance (SOAR) and Antimicrobial Testing Leadership and Surveillance (ATLAS). For common RTIs, clinicians use a range of international and national guidelines. However, a more standardized inclusive approach to developing local guidelines, using up-to-date local surveillance data from community-acquired infections, could make guidelines more locally relevant. This would encourage more appropriate antibiotic prescribing and improve adherence. This would, in turn, potentially limit AMR development and improve patient outcomes.